The Busy Book as an Interactive Media for Teaching the Sasak Language to Young Children - Baiq Nur Khairunnisa Haqiqi; I Made Suarjana; Dewa Gede Firstia Wirabrata (Jurnal Pendidikan Anak Usia Dini Undiksha, 2026)
Sasak language instruction in Early Childhood Education (ECE) is currently dominated by repetitive, static, and unengaging worksheet activities, leading to low interest, participation, and vocabulary exposure in children. This research aimed to develop and evaluate the feasibility of an interactive busy book as a solution. The study employed a Research and Development (R&D) approach using the ADDIE model, concentrating on the analysis, design, and development phases. The analysis phase involved examining the curriculum, learner characteristics, and the need for language preservation. The design phase focused on establishing objectives, selecting vocabulary content, and creating activity blueprints. In the development phase, a prototype was produced and subsequently revised based on expert feedback. The study’s subjects were confined to three validation groups: a subject matter expert (Sasak language specialist), a media expert (instructional technology lecturer), and a practitioner (ECE educator), who assessed the product's quality. Data were gathered via structured validation questionnaires and analyzed using a descriptive quantitative-qualitative method. The final product is a flannel busy book that introduces basic Sasak vocabulary through contextual, sensorimotor play activities. Validation results yielded average scores of 5.0 from the subject matter expert, 4.9 from the media expert, and 5.0 from the practitioner, all within the “excellent” category. Despite minor suggestions for visual layout improvements, the busy book was deemed highly feasible for use after revisions. In conclusion, the medium is valid in content and design and effectively addresses learning stagnation. The implication is that the busy book can improve children’s language, support Sasak language revitalization, and guide game-based local content curricula. Further research should test its effectiveness in broader populations.